2008
DOI: 10.1016/j.pain.2008.07.014
|View full text |Cite
|
Sign up to set email alerts
|

Analgesic effect in rodents of native and recombinant Phα1β toxin, a high-voltage-activated calcium channel blocker isolated from armed spider venom

Abstract: Calcium influx through neuronal voltage-sensitive calcium channels (VSCC S) mediates nociceptive information in the spinal dorsal horn. In fact, spinally administered VSCC S blockers, such as omega-conotoxin MVIIA, have analgesic effect apart of their low therapeutic index and many side effects. Here we study the analgesic potential of Ph alpha 1beta, a calcium channel blocker, in rodent models of acute and persistent pain. Spinally administered Ph alpha 1beta showed higher efficacy and long-lasting analgesia … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
102
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(103 citation statements)
references
References 37 publications
0
102
1
Order By: Relevance
“…N-and P/Q-type channels blockers are suggested to lead to a clinical improvement of cognitive decline in Alzheimer's patients (Amenta et al, 2009) and to an absence of seizures in epilepsy (Zamponi et al, 2010). Additionally, peptide neurotoxins found in animal venoms have received great interest and have been related to neuropathic pain control (Souza et al, 2008;Rigo et al, 2013a) and the management of cancer-associated pain (Rigo et al, 2013b) in animal models during P/Q-and N-type modulation. Pinheiro et al (2006Pinheiro et al ( , 2009 showed a neuroprotective role for a P/Q-type blocker in an in vitro model of hippocampal ischemia induced by oxygen and glucose deprivation; the neurotoxins prevented neuronal death by inhibition of glutamate release.…”
Section: Voltage-gated Calcium Channelsmentioning
confidence: 99%
“…N-and P/Q-type channels blockers are suggested to lead to a clinical improvement of cognitive decline in Alzheimer's patients (Amenta et al, 2009) and to an absence of seizures in epilepsy (Zamponi et al, 2010). Additionally, peptide neurotoxins found in animal venoms have received great interest and have been related to neuropathic pain control (Souza et al, 2008;Rigo et al, 2013a) and the management of cancer-associated pain (Rigo et al, 2013b) in animal models during P/Q-and N-type modulation. Pinheiro et al (2006Pinheiro et al ( , 2009 showed a neuroprotective role for a P/Q-type blocker in an in vitro model of hippocampal ischemia induced by oxygen and glucose deprivation; the neurotoxins prevented neuronal death by inhibition of glutamate release.…”
Section: Voltage-gated Calcium Channelsmentioning
confidence: 99%
“…As such, regulation of CaV2.2 expression and function is posited to have a major impact on the presentation of multiple pain states. Indeed, inhibition of CaV2.2 by synthetic conopeptides provides analgesic relief in a variety of platforms (3)(4)(5)(6). However, given the importance of CaV2.2 integrity in peripheral and central synapses, directly targeting channel function is complicated by a myriad of adverse side effects (7)(8)(9).…”
mentioning
confidence: 99%
“…This is the first study that evaluates the neuroprotective effects of ω-conotoxin MVIIA in vivo in rats subjected to SCI. In this experiment, MVIIA concentrations were chosen from 5 to 20μM of MVIIA due to the variability of doses reported in the literature, mostly antinociceptive studies where concentrations of 3 to 200μM showed efficacy in blocking the N-type VDCC (SOUZA et al, 2008;HAMA & SAGEN, 2009;SOUZA et al, 2011;, with side effects as a limiting factor. In agreement with HAMA &SAGEN (2009), the lowest dose (5μM) had no complications.…”
Section: Resultsmentioning
confidence: 99%
“…Mean (± standard deviation) concentration of glutamate in the cerebrospinal fluid compared to placebo (100) were 124.14%±22.46 (SHAM), 100.1%±58.21 (5μM MVIIA), 95.92%±89.75 (10μM MVIIA) and 52.02%±35.25 (20μM MVIIA) ( Figure 1B). Despite the observation of MVIIA in reducing glutamate at early times (SOUZA et al, 2008;GONÇAVES et al, 2011), some authors pointed out that this fact is not the only implicated in toxin neuroprotection (VALENTINO et al, 1993), since high doses are required for regulation of glutamate release in less than 50% when compared to effective inhibitors levels (BOWERSOX et al, unpublished data, 1999cited by WANG & BOWERSOX, 2000.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation